Lamotrigine and levetiracetam exert a similar modulation of TMS‐evoked EEG potentials - Premoli, Isabella (Epilepsia, 2016)
OBJECTIVE: Antiepileptic drug (AED) treatment failures may occur because there is insufficient drug in the brain or because of a lack of relevant therapeutic response. Until now it has not been possible to measure these factors. It has been recently shown that the combination of transcranial magnetic stimulation and electroencephalography (TMS‐EEG) can measure the effects of drugs in healthy volunteers. TMS‐evoked EEG potentials (TEPs) comprise a series of positive and negative deflections that can be specifically modulated by drugs with a well‐known mode of action targeting inhibitory neurotransmission. Therefore, we hypothesized that TMS‐EEG can detect effects of two widely used AEDs, lamotrigine and levetiracetam, in healthy volunteers. METHODS: Fifteen healthy subjects participated in a pseudo‐randomized, placebo‐controlled, double‐blind, crossover design, using a single oral dose of lamotrigine (300 mg) and levetiracetam (3,000 mg). TEPs were recorded before and 120 min after drug intake, and the effects of drugs on the amplitudes of TEP components were statistically evaluated. RESULTS: A nonparametric cluster‐based permutation analysis of TEP amplitudes showed that AEDs both increased the amplitude of the negative potential at 45 msec after stimulation (N45) and suppressed the positive peak at 180 msec (P180). This is the first demonstration of AED‐induced modulation of TMS‐EEG measures. SIGNIFICANCE: Despite the different mechanism of action that lamotrigine and levetiracetam exert at the molecular level, both AEDs impact the TMS‐EEG response in a similar way. These TMS‐EEG fingerprints observed in healthy subjects are candidate predictive markers of treatment response in patients on monotherapy with lamotrigine and levetiracetam.